Efeito da adição do estrôncio no tratamento térmico da liga de alumínio 6063 - Almeida, Fernanda Leite (2021)
The demand for aluminum has been growing in recent decades due to its wide applicability in several industrial sectors, mainly due to the fact that aluminum and its alloys have a relatively low density compared to other metallic alloys. The aim of this work was to characterize the influence of strontium in the heat treatment of homogenization of aluminum billets in Al-Si-Mg alloys. The homogenization heat treatment guarantees the reduction of microsegregations and the transformation of alloy intermetallics, improving the mechanical deformation process and reducing the formation of surface defects in the extruded profile. In this work, batches of billets from alloy 6063 with and without strontium were produced on an industrial scale and subjected to heat treatments at 580°C in the periods of 0 h, 1 h, 1.5 h, 2 h and 3 h, and cooled with forced air. The strontium efficiency was evaluated by the dissolution methods in a static bath and through the injection of strontium alloy rods continuously in the bath. The inclusion analysis was performed using the PoDFA (Porous Disc Filtration Analysis) methodology, and the results showed little strontium influence on the loss of effectiveness of the grain refiner and consequently on the generation of additional inclusions in the produced alloy. The hardness of the alloys was also measured and it was observed that strontium did not influence the values ​​obtained. Metallographic analyzes were performed, which pointed out the non-influence of the size of the grain size and inverse segregation as a function of the time of the heat treatment. However, the intermetallic transformation is improved with the time of exposure of the metal to the heat treatment and with the addition of strontium in the alloy. Differential scanning calorimetry (DSC) analyzes showed that the addition of strontium did not influence the transformation of the alloy precipitate structure.